FINANCIAL RESULTS AND MARKET VALUE OF ENTREPRENEURIAL ENTITIES - Razzakov Jaloliddin Alijon ógli (Web of Journals Publishing, 2024)
The relationship between financial results and market value is crucial for entrepreneurial entities striving to achieve long-term sustainability and growth. This paper explores the impact of financial performance indicators such as profitability, revenue growth, and capital structure on the market value of entrepreneurial entities. By analyzing the interaction between these variables, the study aims to understand how effective financial management can enhance a business’s overall valuation in a competitive market.
Keywords: Financial results, Market value, Entrepreneurial entities, Profitability, Valuation.